Pathogen Profile of Patients with Sepsis in Internal Medicine, Dr. Hasan Sadikin General Hospital, Bandung 2013 - Fauzi, Afiq Syazwan; Sumardi, Uun; Tristina, Nina (Althea Medical Journal, 2016)
Background: Sepsis is a continuous disease which begins with systemic inflammatory response syndromeÂ (SIRS), seen in association with a large number of clinical conditions. These include infectious insults thatÂ produce SIRS, such as pancreatitis, ischemia, multiple traumas and tissue injury, hemorrhagic shock, immunemediatedÂ organ injury, and the exogenous administration of such putative mediators of the inflammatoryÂ process as tumor necrosis factor and other cytokines. A frequent complication of SIRS is the development ofÂ organ system dysfunction, including such well-defined clinical conditions as acute lung injury, shock, renalÂ failure, and multiple organ dysfunction syndrome (MODS). Hence, this study was conducted to identify theÂ pathogen profile that often causes sepsis.Methods: A retrospective study was performed to 152 medical records of patients diagnosed as sepsisÂ from Internal Medicine Department Dr. Hasan Sadikin General Hospital from January 2013 to DecemberÂ 2013. The variables observed from the medical records were age, sex, comorbidity, main infection, cultureÂ sample, type of gram bacteria, resistant bacteria, and antibiotic susceptibility test. After data collection wasÂ completed, the data were analyzed using computer. The data were presented in percentage.Results: Sepsis in male was higher than female. Highest comorbid was chronic kidney disease (CKD). TheÂ main infection was health care acquired pneumonia (HCAP). Highest pathogen that caused sepsis wasÂ Escherichia coli and highest multidrug-resistant organism (MDRO) was extended spectrum beta-lactamase(ESBL) Escherichia coli.Conclusions: The most common pathogen that causes sepsis is Escherichia coli. [AMJ.2016;3(2):200â5]DOI:Â 10.15850/amj.v3n2.785